Major Hindu Festivals: A Christian Appreciation - Tom, Mari (Journal of Dharma, 1992)
Subash Ananda, Major Hindu Festivals-A Christian Appreciation, Bombay : St. Paul Publications, 1991, pp. 144, Rs. 32.00.